Online sexual health survey implementation: Practical lessons from a comparative, mixed-methods analysis of 30 countries - Hanna Saltis; Fiorella Farje; Simukai Shamu; Raquel Gomez; Johanna Schröder; Priya Kosana; Sharyn Burns; Jacqueline Hendriks; Olivia Williams; Kristien Michielsen; Joseph D. Tucker (PLoS ONE, 2026)
Online surveys are potentially useful for sexual and reproductive health. However, there are many persistent problems related to online sexual and reproductive health surveys. This study aims to understand online recruitment, dissemination and implementation as part of the International Sexual Health And REproductive health (I-SHARE) consortium online sexual health survey. This study used a mixed-methods, cross-sectional, multi-country design. We used survey data from the I-SHARE study and organised a separate implementation survey completed by I-SHARE country leads. A total of 24,004 participants in 30 countries responded to the I-SHARE survey. All countries implemented the I-SHARE survey online and most (n = 27, 90%) used convenience sampling. Social media promotion (n = 27, 90%), and partner organisations sharing (n = 21, 70%) were the most common recruitment methods. Twenty-nine countries responded to the implementation survey. We identified three themes related to online survey implementation: (1) Adaptation and flexibility highlighted research teams’ responsiveness to rapidly changing contexts; (2) Better together: Partnerships illustrated the importance of multi-sectoral collaboration; and (3) Same but different: the heterogeneity of countries captured the ongoing tension between creating a standardised tool while honouring countries’ unique socio-health climates and responses to the unfolding pandemic. This data demonstrates the potential for using online sexual health surveys in diverse settings. Our study suggests the need for greater consideration of bias related to communication, especially the digital divide, when designing and implementing online surveys.